Analisis Literatur Tingkat Kesulitan Guru dalam Membuat Modul Ajar - Meliny Meliny; Santiani Santiani (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Through a comprehensive literature analysis, this article aims to explore the various challenges faced by teachers in compiling teaching modules based on the Independent Curriculum and identify the factors causing these difficulties. An analytical approach to empirical findings is expected to provide a basis for formulating strategies for developing teacher competencies in overcoming these challenges, as also encouraged by various previous studies. The results of the study indicate that the level of difficulty for teachers in creating teaching modules does not only come from a lack of technical understanding of the module components, but is also influenced by external factors such as minimal mentoring, limited resources, and challenges in accommodating the diversity of students. Existing literature research underlines the importance of synergy between improving teacher competency and education policy support to create an environment that supports innovation in learning. Therefore, teacher competency development strategies need to be designed comprehensively by integrating practical training, intensive mentoring, and provision of supporting infrastructure as strategic steps in overcoming obstacles to compiling teaching modules based on the Independent Curriculum.